2012
DOI: 10.1016/j.jvs.2011.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Loss of lymphatic vessels and regional lipid accumulation is associated with great saphenous vein incompetence

Abstract: The accumulation of LPC (1-acyl 16:0) and PC (diacyl 16:0/20:4) in the VV intima and media may be associated with chronic inflammation, leading to VV tissue degeneration. Furthermore, insufficient lipid drainage by lymphatic vessel may be responsible for accumulation of lipid molecules and subsequent vein wall degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In collaboration with other researchers, we have recently developed a matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) imaging system and techniques to provide a comprehensive characterization of the molecules within a tissue sample [9][10][11] . MALDI-IMS enables the visualization of individual molecules on vascular tissue sections, without requiring antibodies, staining or other complicated preparations of tissue samples [12][13][14][15] . Of specific application to this study, MALDI-IMS provided a direct visualization of lipid molecules allowing us to identify their nature and distribution within the tissue sample.…”
mentioning
confidence: 99%
“…In collaboration with other researchers, we have recently developed a matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) imaging system and techniques to provide a comprehensive characterization of the molecules within a tissue sample [9][10][11] . MALDI-IMS enables the visualization of individual molecules on vascular tissue sections, without requiring antibodies, staining or other complicated preparations of tissue samples [12][13][14][15] . Of specific application to this study, MALDI-IMS provided a direct visualization of lipid molecules allowing us to identify their nature and distribution within the tissue sample.…”
mentioning
confidence: 99%
“…Long-chain polyunsaturated fatty acids (LC-PUFAs) as fatty acyl residues present in PCs have been described to be precursors of lipid inflammatory mediators after their release by the activation of phospholipases. The LC-PUFAs could be involved in inflammatory responses [31], such as AA (20:4), one kind of n -6 series fatty acid, which was reported to participate in inflammatory reaction [32], and the elevated level of AA-contained PCs were considered related to chronic inflammation in other studies [33, 34]. In our study, PC (16:0/20:4) and PC (18:2/20:4) containing AA were increased in War-T region.…”
Section: Discussionmentioning
confidence: 99%
“…19) Furthermore, we found that there are lymph vessels in the great saphenous vein wall, but the number of lymph vessels in the great saphenous vein wall was lower in the VV patients with prominent cutaneous symptoms. 21) Although the primary cause of inflammation in such tissues is not yet understood, the observed reduction in the number of lymphatic vessels could have been caused by lymphatic vessel cell apoptosis (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%